Efficacy of Piperazine Dihydrochlloride Against Toxocara Vitulorum in Buffalo Calves - Satrija, Fadjar; Ridwan, Yusuf; Budi Retnani, Elok (Jurnal Veteriner, 2012)
A study was conducted to evaluate the efficacy of piperazine dihydrochloride against natural infectionof Toxocara vitulorum in buffalo calves. In the first trial 60 based on fecal ascarid egg count and bodyweight naturally infected calves were, allocated into four groups. Three groups (groups B, C and D) weregiven piperazine dihydrochloride per os at dose levels of 200, 300 and 500 mg per kg body weight,respectivelythe remain group is non-treated controls. Piperazine treatment reduced egg excretion levels at98 to 99 per cent within 7, 14 and 21 days after treatment. Depite no significant differences were foundamong the three doses, highest egg count reductions were observed in calves given the drug 300 mg per kgbodyweight. The second trial were conducted using 10 additional calves. Piperazine significantly reducedT vitulorum egg excretion by 93% within 7 days post the treatment.
Keywords: buffalo calves, piperazine, Toxocara vitulorum